Dampak Covid-19 Terhadap Siswa Kelas VII SMP Negeri 16 Depok pada Pembelajaran PJOK - Putri, Alicia Melinda; Yusuf, Gelardhy (Universitas Singaperbangsa, 2022)
This study aims to determine the Impact of Covid-19 on Class VII Students of SMP Negeri 16 Depok in PJOK Learning and prove that the impact of Covid-19 on class VII students at SMPN 16 Depok City is experiencing a very serious problem. This research is a quantitative descriptive research. The population of this research is seventh grade students at SMPN 16 Depok City with a total sample of 22 students. The research instrument used a questionnaire consisting of 5 statements. The analysis technique for this research data uses a Likert Scale. So this shows that there is an impact on class VII students during the Covid-19 pandemic, especially on PJOK learning